Bronze Vessels discovered in the Loch of Leys (Proceedings of the Society of Antiquaries of Scotland, 1852)
J.H. Burnett communicated the discovery of several objects found submerged in the Loch of Leys when it was drained. They had also found an artifical island that had once had a great building upon it, which local legends suggested was once a castle. As the excavation continued, they uncovered cooking vessels, especially kettles, two of which Sir Alexander Burnett presented to the Society. It is remarked that the vessels are very like those pictured in medieval manuscripts.